1991
DOI: 10.1055/s-0038-1648188
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Blood Clot Lysis on the Mode of Transport of Urokinase into the Clot - A Magnetic Resonance Imaging Study in Vitro

Abstract: SummaryMagnetic resonance imaging was employed to study the dependence of clot lysing patterns on two different modes of transport of urokinase into whole blood clots. In one group of clots (nonperfused clots, n1 = 10), access of urokinase to the fibrin network was possible by diffusion only, whereas in the other group (perfused clots, n2 = 10) bulk flow of plasma containing urokinase was instituted through occlusive clots by a pressure difference of 3 .7 kPa (37 cm H2O) across 3 cm long clots with a diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 16 publications
2
52
0
Order By: Relevance
“…1). When a pressure gradient of 1-2 Wdcm of clot length was applied along occlusive cylindrical clots channels of lysed areas penetratedinto non-retracted clots with a velocity of 60-100 mm/h [2] and into retracted clots with a velocity of about 5 mm/h (Fig.2) [3]. Bulk flow of plasminogen and UK into clots thus accelerated the rate of lysis up to 100-fold in comparison to transport by diffusion.…”
Section: Delivery Of Plasminogen and Plasminogen Activator Into The Clotmentioning
confidence: 99%
“…1). When a pressure gradient of 1-2 Wdcm of clot length was applied along occlusive cylindrical clots channels of lysed areas penetratedinto non-retracted clots with a velocity of 60-100 mm/h [2] and into retracted clots with a velocity of about 5 mm/h (Fig.2) [3]. Bulk flow of plasminogen and UK into clots thus accelerated the rate of lysis up to 100-fold in comparison to transport by diffusion.…”
Section: Delivery Of Plasminogen and Plasminogen Activator Into The Clotmentioning
confidence: 99%
“…8 It has been suggested that this variation in response to treatment depends on clot size, composition, and source 33 and that old platelet-rich, well-organized thrombi formed under flow conditions are more resistant to lysis than fresh fibrin and red cell-rich clots formed under stasis. [34][35][36] It is important to highlight that citrated blood is used and ROTEM parameters measured reflect the activity of rt-PA on the clot that occurs ex vivo at the time of citrate reversal. Hence, we cannot be certain that these measurements exactly reflect the effect of rt-PA on clot kinetics in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the changes in clot composition over time result in older fibrin-rich clots to be more organized and hence more resistant to thrombolysis, decreasing the likelihood for the occluded arteries to be recanalized. [19][20][21][22] Recanalization is associated with a significant survival benefit. 7,8 Our study showed that 30/41 (73.2%) patients who were recanalized survived at 90 days, compared to 3/8 (37.5%) non-recanalized patients (p = 0.094).…”
Section: Discussionmentioning
confidence: 99%
“…Fresh newly formed clots are more red blood cell dominant and less resistant to thrombolysis, while older clots are more fibrin-rich and well-organized and hence more resistant to thrombolysis. [19][20][21][22] Furthermore, shortening the delay to intervention is vital in ensuring the survival of penumbral tissue. 23 Successful intervention to attenuate the growth of the ischaemic core positively contributes to good clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%